Społeczne i gospodarcze konsekwencje zarazy ziemniaczanej w latach czterdziestych XIX w. - Myszczyszyn, Janusz (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2014)
In 1845/1846 a so far unknown species arrived in Europe – the fungus Phytophthora infestans. Phytophthora infestans causes the late blight of the potato. The blight became known as the potato famine and was a historic and tragic disaster. The infected potato plants and tubers rotted and became black. Potato crops shrivelled to about 70–80% in Ireland, 30–50% in Prussia and Belgium. The infamous to spread in the following years and it is a hazard to agriculture until today. On the other hand, this period, and 1846/1847 in particular, was also one of poor wheat and rye harvests throughout much of Europe. The combination of poor potato and grain harvests resulted in a subsistence crisis in Europe. The price increases led to panic, popular unrest, privation. Wherever the potato bulked large in the people’s diet, its failure resulted in excess mortality (Ireland, Flanders, the Netherlands, Prussia).